Gender and Andean natural medicine - Valdivieso Eguiguren, Ligia (2001)
I do not have any degree in medicine, but from life I have been introduced, through courses, contacts and readings, in various alternative medicines: "fangotherapy" (healing with mud), "hydrotherapy" (healing with water), "herbal " (healing with herbs), "Andean medicine" (which I will talk about later), "microdosing" (healing with small doses of curative remediation), "cerebral thermoregulation therapy" (with aluminum and copper plates), "pleasant medicine " (based on the harmony of the person with the universe), "physioenergetics" (diagnostic therapy), "hosteopathy" (through touches on the spine).